2013
DOI: 10.1680/macr.12.00037
|View full text |Cite
|
Sign up to set email alerts
|

Prestressed concrete thermal behaviour

Abstract: The structural fire safety capacity of concrete is very complicated because concrete materials have considerable variations. Constitutive relationships for prestressed normal-strength concrete (NSC) and high-strength concrete (HSC) subjected to fire are needed to provide efficient modelling and to meet specific fire-performance criteria of the behaviour for prestressed concrete structures exposed to fire. In this paper, formulations for estimating the parameters affecting the behaviour of unconfined prestresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Second, the slow rate of heating restricted obvious spalling. Third, the ITZs between fibers and surrounding fresh paste provided sufficient pathway for the vapor, contributing to mirror spalling behavior …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the slow rate of heating restricted obvious spalling. Third, the ITZs between fibers and surrounding fresh paste provided sufficient pathway for the vapor, contributing to mirror spalling behavior …”
Section: Resultsmentioning
confidence: 99%
“…Third, the ITZs between fibers and surrounding fresh paste provided sufficient pathway for the vapor, contributing to mirror spalling behavior. 21,[54][55][56][57][58][59][60][61][62][63][64][65][66] Figure 7 presented that mass loss for PP fiber-reinforced LWSCC increased by higher fiber ratio especially higher than 600 C. The mass losses were less than 0.1% of selfweight at 100 C for all the mixes, which suggested that at 100 C minimal free water was lost due to dehydration of the cement paste. For the 300 C heating treatment, the mass loss LWSCC mixes with various fiber ratios raised dramatically to 4.6% of self-weight.…”
Section: Hardened Mechanical Propertiesmentioning
confidence: 99%
“…In the stressed test, the concrete specimen is subjected to preload before and throughout the heating process [ 18 ], and the most obvious difference between the stressed and unstressed concrete is that the compressive strength is higher when the specimen is stressed during heating than that of unstressed concrete during heating, which was first reported by Malhotra [ 19 , 20 ]. In order to investigate the effect of high temperature on stressed concrete, Abram [ 21 ], Khoury [ 22 ], and Schneider [ 23 ] conducted experimental tests on the stressed and unstressed concrete and came to the same conclusion as Malhotra [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can however be argued that HSC is more prone to spalling due to its lower porosity, thereby contributing to the increased likelihood of high pressure developing within the concrete structure [8]. On another hand, the effect of high temperature on the reinforcing steel was by others [9,10]. Youssef and Moftah [2] reported reinforcing steel is much more sensitive to high temperatures than concrete.…”
Section: Introductionmentioning
confidence: 99%